AB0199 Serum Levels, Tissue Expression and Cellular Secretion of Macrophage Migration Inhibitory Factor (MIF) in Limited and Diffuse Systemic Sclerosis. (9th June 2015) - Corallo, C.; Cutolo, M.; Montella, A.; Chirico, C.; Magliocca, A.; Nuti, R.; Giordano, N.
Abstract : Background: Macrophage-Migration-Inhibitory-Factor (MIF) is a proinflammatory cytokine that has been demonstrated to be responsible of dysregulated apoptosis of fibroblasts in a variety of inflammatory-fibrotic diseases, including systemic sclerosis (SSc) (1). Moreover, MIF might contribute to the inflammatory stage of vasculopathy in SSc (2). Objectives: To investigate serum levels, tissue expression and cellular secretion of MIF in patients with limited-(lSSc) and diffuse-(dSSc) SSc and to associate MIF levels to clinical manifestation of the disease. Methods: 10 lSSc-patients, 10 dSSc-patients and 10 controls were enrolled. MIF serum levels were assayed by ELISA. MIF and its receptors CD74/CD44 were evaluated by immunohistochemistry on skin biopsies from patients with dSSc, lSSc (affected and not-affected skin) and controls. MIF levels were assessed (ELISA) in supernatants of dermal-microvascular-endothelial-cells (MVECs) and in control-(CTR), not-affected-lSSc-(NA) and affected-(SSc) fibroblasts treated for 48h with 10% control-serum and 10% SSc-serum. MIF supernatant (ELISA) and mRNA (quantitative-real-time-PCR) levels were determined in SSc-dermal-fibroblasts and in control-dermal-fibroblasts untreated or stimulated with Bleomycin (50mU/ml) at 6h-24h-48h. MIF levels were also associated to the presence of pulmonary hypertension (PH) and digital ulcers (DU). Results: Serum MIF was significantly higher in dSSc (18.7±4.1 ng/ml, p<0.001) in lSSc (10.4±4.4 ng/ml, p<0.001) patients respect to controls (2.6±1.4 ng/ml). Enhanced MIF immunoreactivity was found in keratinocytes, fibroblasts, endothelium, sebaceous/sweat-glands from lSSc/dSSc affected skin. Faint MIF immunoreactivity was found in control skin and not-affected skin of lSSc-patients. No differences were found in CD74/CD44 receptors' analysis among control and dSSc/lSSc affected and not-affected skin. MVECs and fibroblasts (CTR, NA and SSc) showed higher MIF secretion, when stimulated with SSc-serum respect to control-serum (p<0.001). MIF mRNA levels significantly increased at 6h (p<0.001) and decreased at 48h (p<0.001) in control fibroblasts treated with Bleomycin compared to control untreated ones. Simultaneously, MIF-supernatant-protein-levels increased after 48h (p<0.01) in Bleomycin-treated fibroblasts respect to untreated ones. Finally, patients with PH and DU showed higher MIF levels than patients without those manifestations (p<0.005). Conclusions: These results suggest that MIF could be involved in the development of SSc skin fibrosis, probably interfering with dermal fibroblast homeostasis. Moreover, high MIF levels seem to be related to the degree of vascular involvement in SSc. References: Kim JY, Kwok SK, Hur KH, Kim HJ, Kim NS, Yoo SA, Kim WU, Cho CS. Up-regulated macrophage migration inhibitory factor protects apoptosis of dermal fibroblasts in patients with systemic sclerosis. Clin Exp Immunol 2008;152(2):328-35. Becker H, Willeke P, Schotte H, Domschke W, Gaubitz M. Macrophage migration inhibitory factor may contribute to vasculopathy in systemic sclerosis. Clin Rheumatol 2008;27(10):1307-11. Disclosure of Interest: None declared